Study on Compact Powder Formulation from Fermented Rice Powder (Bedak Sejuk) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Bedak sejuk is a local cosmetic product produced from the natural fermentation of rice and can be placed in a group of green cosmetic products. Current traditional forms of production in beads require change for modern applications i.e. compact face powder. For that reason, the initial study was executed on the formulation to change it into compact powder based on three selected parameters which were bedak sejuk contents, binding agent concentrations (ethanol)  and the amount of oil-absorbing agent (virgin coconut oil) used. Data obtained were analyzed using the One Factor At Time (OFAT) based on three tests which are drop test (height and weight) and its capacity to absorb oil. Based on the results, it is found that the best formulation for compact powder formulation (lowest cracking) was found at 50% bedak sejuk composition with 0.5 mol binding agent and 0.3 ml virgin coconut oil. This study indicates that bedak sejuk has the potential to be modernized for modern applications.
Keywords: Bedak sejuk; Compact powder; Binding agent; Oil absorption; Green cosmetic